2017
DOI: 10.1097/mog.0000000000000396
|View full text |Cite
|
Sign up to set email alerts
|

Luminal chemosensing in the gastroduodenal mucosa

Abstract: Purpose of review We report recently published knowledge regarding gut chemosensory mechanisms focusing on nutrient-sensing G protein-coupled receptors (GPCRs) expressed on gut enteroendocrine cells (EECs), tuft cells, and in afferent nerves in the gastroduodenal mucosa and submucosa. Recent findings Gene profiling of EECs and tuft cells have revealed expression of a variety of nutrient-sensing GPCRs. The density of EEC and tuft cells is altered by luminal environmental changes that may occur following bypas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Recent studies that showed the presence of plasma membrane receptors for nutrients outside the gustatory system, especially in the gut, suggesting a much more complex role of nutrients in the control of gut function, appetite, and even emotional conditions. [1][2][3][4][5][6][7][8] The majority of the research on the receptors for chemosensation has focused on EECs of gut mucosa. Plasma membrane GPCRs for umami and sweet agonists comprise heterodimers of T1R subtype; T1R1/T1R3 for umami and T1R2/T1R3 for sweet receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies that showed the presence of plasma membrane receptors for nutrients outside the gustatory system, especially in the gut, suggesting a much more complex role of nutrients in the control of gut function, appetite, and even emotional conditions. [1][2][3][4][5][6][7][8] The majority of the research on the receptors for chemosensation has focused on EECs of gut mucosa. Plasma membrane GPCRs for umami and sweet agonists comprise heterodimers of T1R subtype; T1R1/T1R3 for umami and T1R2/T1R3 for sweet receptors.…”
Section: Discussionmentioning
confidence: 99%
“…GI motility is controlled by neurohumoral agents released from the autonomic and enteric nervous system, glial cells, and enteroendocrine cells (EEC), which modulate the contractility of SMCs. [3][4][5][6][7][8] These new roles for nutrients and their receptors have made a significant impact in the field of GI motility and secretion. 2 The effects of nutrients have recently been expanded by studies that showed the presence of extra-oral nutrient receptors, especially in the gut, and studies to understand their functional significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While little is known of the mechanisms of response to BCFA in the gut, the responses to SCFAs (mainly acetate, propionate, and butyrate) are mediated through the fatty acid receptor 2 (FFA2) and/or 3 (FFA3) formerly known as GPR43 and GPR41, respectively. These receptors are expressed in a variety of cells in the gut including enteroendocrine cells, adipocytes, pancreatic cells, immune cells, and enteric neurons; however, their expression in smooth muscle has not been studied [4,5,[7][8][9][10][30][31][32][33][34][35]. Similarly, their role in mediating the response to BCFA has not been studied in any of these cell types in any detail.…”
Section: Discussionmentioning
confidence: 99%
“…Recent interest has been directed at these SCFA because of their potential role in gut function, glucose homeostasis, appetite, regulation of metabolism, inflammation and immune competence, as well as tumorigenesis and colon cancers. These have been the topic of many recent reviews [3,5,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%